THE CULTURE MARGINALITY IN THE BASIC SPHERE OF IDENTITY - Грушко, Е. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The phenomenon of culture marginality in the context of the basic sphere of identity is represented in the article. Marginality building force of human experience is exposed. It illuminates the modi of dissimilarity of the one to others. Creative potentiality of the culture marginality is analyzed at the individual and social levels.